Increasing toughness and tensile strength of an epoxy–diamine system using an inorganic ultra-accelerator. Issue 65 (16th July 2015) - Mirmohseni-Namin, Abdolreza; Nikafshar, Saeid; Mirmohseni, Farid
<x xml:space="preserve">Abstract</x> Epoxy resins are a class of thermoset materials with extensive structural and composite applications.